Pengaruh Akuntabilitas, Time Pressure Dan Pemahaman Sistem Informasi terhadap Kualitas Audit dengan Due Professional Care sebagai Variabel Intervening - Silvia, Riska; Hanum, Zulia (Politeknik Ganesha Medan, 2024)
The study aims to examine and assess how comprehension of accountability, time pressure, and understanding of information systems affect audit quality, with due professional care acting as a mediator. It employs an associative approach, utilizing primary data obtained through distributing questionnaires to 173 auditors employed at a Public Accounting Office in Medan City. Sample determination followed the Slovin formula. Data analysis involved outer model analysis, inner model analysis, and hypothesis testing using Partial Least Squares (PLS) software version 4.1.0.2. The findings are as follows: (1) Accountability doesn't significantly impact Audit Quality; (2) Accountability significantly impacts Due Professional Care; (3) Time Pressure significantly influences Audit Quality; (4) Time Pressure significantly affects Due Professional Care; (5) Understanding Information Systems significantly impacts Audit Quality; (6) Understanding Information Systems significantly affects Due Professional Care; (7) Due Professional Care significantly impacts Audit Quality; (8) Accountability's impact on Audit Quality through Due Professional Care is not significant; (9) Time Pressure's influence on Audit Quality through Due Professional Care is significant; and (10) Understanding Information Systems' effect on Audit Quality through Due Professional Care is significant.